A transição da escola pública do campo: a experiência da Escola Itinerante Zumbi dos Palmares - Marcondes, Vera Lucia (2017)
This research aims to analyze the process of political-structural transition of Zumbi dos Palmares Itinerant School to Rural Education Municipal School, in order to identify contradictions in this process of moving from an itinerant camp school to a permanent settlement school, under management of the Prefeitura Municipal de Cascavel. Thus, this study proposed the following: to present the history of the struggle for land in the camps and settlements of MST, articulated to the struggle for education; to identify elements and pedagogical fundaments that are present in the political-educational proposal of the Municipal School of Zumbi dos Palmares – and that ensure the continuity of expression of its class commitment; and highlight the control mechanisms and instruments of State interference – as a school maintainer –, responsible for obstacles and contradictions in the school practice. Central problem was the need to understand the progress achieved and what remains as a challenge in the transition process from this itinerant camp school to a permanent settlement school, and particularly the State’s role in this transition. Bibliographic, documentary and field researches have been used as a research methodology. As a result, it was observed that the transition from the itinerant school model to the rural school, already in settlement, was constituted by a permanent and dialectical movement in which the participation and vigilance of the school community needs to be constant and conscious. In the same way, also the collective of educators must remain well trained and engaged in order to understand the historical process to make it an effective part of the transition.